Neonatal birth weight and related factors in south of Iran, Jahrom - Fatemeh Emamghorashi; Seyyed Taghi Heydari (Tehran University of Medical Sciences, 2008)
Objective: This study aimed to determinate the relationship between neonatal birth weight and related factors in Jahrom, Iran. Materials and methods: All women delivering in two hospitals, in which obstetric services were presented, entered the study. In this cross sectional study, 2311 women were enrolled prospectively in a 12- month period during 2006-7. Data were collected during first three post partum days from the following sources: maternal hospital files and charts, interview with the mothers, measurement of anthropometric indices of fathers and the infants. Percentile distribution of birth weight for classified gestational age was calculated. Results: Results showed significant correlation between neonatal birth weight with neonatal gender, maternal age, weight, education and working status. There was no relation between neonatal weight with paternal weight, maternal education and living in urban or rural areas. Conclusion: Neonatal birth weight is affected by neonatal gender, maternal age and weight; education and job.